AZ-140 Microsoft Azure Virtual Desktop - Gordon, Adam (Packt Publishing, 2024)
Begin your journey with an overview of Azure Virtual Desktop, understanding its components, and how it fits within the Azure ecosystem. Each section meticulously breaks down elements such as network connectivity, name resolution, and the use of RDP Shortpath for enhanced connectivity. Discover how to effectively plan resources, manage host pools, session hosts, and automate repetitive tasks to save time and reduce errors. Transition into advanced topics like identity and security management, where you'll tackle identity solutions, role-based access control, and multi-factor authentication to secure your virtual desktop environment. Learn about integration with Microsoft Defender for robust security and the implementation of necessary protocols to protect data and infrastructure. Finally, focus on optimizing user experience and application management through FSLogix, device redirection, and session management strategies. Deep dive into application delivery, including MSIX app attach and RemoteApps, ensuring seamless access and operation. The course culminates in monitoring and maintaining your AVD setup using Azure's monitoring tools, autoscaling features, and disaster recovery plans, preparing you to handle real-world scenarios efficiently.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Azure (Computing platform) -- Study guides -- Examinations; Virtual computer systems; Microsoft Azure (Plateforme informatique); Examens; Guides de l'étudiant; Systèmes virtuels (Informatique); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet